2015
DOI: 10.1042/bj20141078
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cell-derived vascular smooth muscle cells: methods and application

Abstract: Vascular smooth muscle cells (VSMCs) play a major role in the pathophysiology of cardiovascular diseases. The advent of induced pluripotent stem cell (iPSC) technology and their capability to differentiation into virtually every cell type in the human body make this field a ray of hope for vascular regenerative therapy and for understanding disease mechanism. In this review, we first discuss the recent iPSC technology and vascular smooth muscle development from embryo and then examine different methodology to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 82 publications
(108 reference statements)
1
41
0
Order By: Relevance
“…The WBS-hiPSC-SMC phenotype was rescued with the use of rapamycin, which inhibits smooth muscle proliferation through the mammalian target of rapamycin (mTOR) pathway (80). This result supports the testing of rapamycin in treatment of individuals with WBS and represents an example of the use of hiPSCs for modeling of diseases associated with smooth muscle proliferation and for the discovery of treatment modalities to be tried in the clinic (81). In attempts to model disease in a dish, hiPSC-SMCs were derived from patients with supravalvular aortic stenosis (82); hiPSC-differentiated cardiomyocytes were derived from patients with the LEOPARD syndrome (83); and hiPSC-ECs were derived from patients with the moyamoya disease (idiopathic cerebrovascular disease) (84).…”
Section: Models and Mechanismssupporting
confidence: 72%
“…The WBS-hiPSC-SMC phenotype was rescued with the use of rapamycin, which inhibits smooth muscle proliferation through the mammalian target of rapamycin (mTOR) pathway (80). This result supports the testing of rapamycin in treatment of individuals with WBS and represents an example of the use of hiPSCs for modeling of diseases associated with smooth muscle proliferation and for the discovery of treatment modalities to be tried in the clinic (81). In attempts to model disease in a dish, hiPSC-SMCs were derived from patients with supravalvular aortic stenosis (82); hiPSC-differentiated cardiomyocytes were derived from patients with the LEOPARD syndrome (83); and hiPSC-ECs were derived from patients with the moyamoya disease (idiopathic cerebrovascular disease) (84).…”
Section: Models and Mechanismssupporting
confidence: 72%
“…It is known that resident vascular stem cells participate in the repair of vessel damages using its ability to undergo differentiation into cell types such as endothelial cells and SMCs . Moreover, the development or repair of vascular damages is affected by whether the stem cells differentiate into endothelial cells or SMCs . It has been suggested that stem cell differentiation into endothelial cells may diminish the thickness of neointima layers .…”
Section: Discussionmentioning
confidence: 99%
“…Specifics of the exact SC differentiation protocols is beyond the scope of this review and can be found elsewhere [21]. …”
Section: Advances In Stem Cell-derived Vascular Modelsmentioning
confidence: 99%